TINJAUAN KESANTUNAN BERBAHASA DALAM IJAB DAN SYAIR SAWER PADA UPACARA NGAROT - Ade Mulyanah (Fakultas Seni Rupa dan Desain ITB, 2011)
This paper is a qualitative study using descriptive methods. The purpose of paper provides an overview of civility and poetic language in the